The Nutritional Profile of Root Vegetables Through Spontaneous Fermentation with Apples: Amino Acid Composition and Microbial Dynamics - Iwona Gientka; Alicja Synowiec; Katarzyna Pobiega; Patrycja Staniszewska; Joanna Perkowska; Marcelina Procyk; Bartosz Igor Pokrywczyński; Monika Janowicz (Fermentation)
To diversify fermented plant-based products, vegetables can be fermented with fruits. This study aimed to evaluate the effect of spontaneous fermentation on the amino acid nutritional profile of sliced carrot (Daucus carota) and celeriac (Apium graveolens), with and without the addition of apple (Malus domestica). Lactic acid bacteria rapidly lowered the pH, ensuring the product’s microbiological stability and safety. The addition of apples to the fermentation of root vegetables had a beneficial effect on maintaining a high number of active lactic acid bacteria. The fermentation process significantly influenced the amino acid composition, reducing the content of acidic amino acids (aspartic acid and glutamic acid) while increasing the levels of several essential amino acids. Leucine was found to be the limiting amino acid in all fermented variants, although its content increased during fermentation. The Essential Amino Acid Index (EAAI) of the fermented products was generally higher in variants with apple (carrot with apple = 1.13, and celeriac with apple = 1.03). The results indicate that the fermentation of root vegetables with apple enhances protein quality and contributes to the development of nutritionally valuable, microbiologically safe fermented foods. This study supports sustainable dietary practices by utilizing locally available root vegetables to create innovative plant-based fermented products.